(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2023)
In our research, we present the effect of adopting the five-year study model in the College of Humanities and Education, Tikrit University, on the academic performance of fourth-year students. The research sample consisted of (30) students, including (15) students in the experimental group and (15) students in the control group. Both groups were rewarded. The variables of chronological age, parents’ educational attainment, and third-stage averages for psychology. Equivalence was done using the chi-square statistical method. After equivalence was conducted, the researcher applied an achievement test, where its validity was verified by presenting it to a group of experienced and specialized people. After that, behavioral objectives were formulated for the psychology topics for the first three semesters scheduled to be taught to the experimental and control groups. Reliability was also extracted. The test.